Indywidualizacja niepewności w społeczeństwie cyfrowym: czy przyszłość pracy stała się teraźniejszością? = Individualisation of uncertainty in the digital society: has the future of work become the present? - Novikova, Kateryna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Rapid technological development and globalization not only increase the unpredictability of the global economy, but also raise questions about the future of work. The article presents selected themes concerning the global discourse on the future of work in the context of collective measures and individualised strategies. The emphasis and recommendations are strongly focused on developing individual skills, entrepreneurship and creativity, which are considered to be unique qualities of the human being.
Keywords: freelancer; autonomia; elastyczność; Solidarność; odpowiedzialność; autonomy; ?exibility; solidarity; responsibility